Exploring the Effects of Acupuncture on Behaviors of Autism Spectrum Disorder Based on the NRG1/ErbB4 Signaling Pathway - ZHUANG Wanyu; HONG Yu; ZHANG Yingying; CHEN Sijie; HUANG Longsheng; KANG Jie (康复学报)
ObjectiveTo explore the effect of acupuncture on the behavioral activities of autism spectrum disorder (ASD) model rats based on the recombinant neuregulin 1/receptor protein-tyrosine kinase erbB-4 signaling pathway and to investigate the possible mechanism by which acupuncture improves the behavioral activities of ASD.MethodsAdult SPF-grade Wistar rats were used. The model was established by intraperitoneal injection of sodium valproate in pregnant female rats at 12.5 days of gestation. Twenty-four ASD model rats were randomly divided into model group, acupuncture group, and NRG1 group, with 8 rats in each group. The NRG1 group was obtained by lateral ventricle NRG1 lentivirus infection on the basis of the ASD model. The acupuncture group was treated at the "Zhi San Zhen" acupoints, with a depth of approximately 1 mm, and the needles were retained for 40 minutes and manipulated once every 10 minutes at each acupoint. The model group and the NRG1 group only simulated the grasping action. The three groups were intervened at the same time every day, once a day, for 14 consecutive days. The behavioral activities of the rats were observed by the three-chamber social test, the open field test, and the Morris water maze. The relative mRNA and protein expression levels of NRG1 and ErbB4 in the frontal lobe of the brain were detected by qPCR and Western blot methods, respectively.ResultsIn the first stage, compared with the model group, the NRG1 group spent more time in contact with the unfamiliar rat 1 (P<0.05); compared with the model group, the acupuncture group and the NRG1 group spent less time in contact with the object (P<0.05). In the second stage, compared with the model group, the acupuncture group and the NRG1 group spent less time in contact with the unfamiliar rat 1 (P<0.05); compared with the model group, the acupuncture group and the NRG1 group spent more time in contact with the unfamiliar rat 2 (P< 0.05). Compared with the model group, the exploration behavior, that is, the frequency of exploration in the middle area, increased in the acupuncture group and the NRG1 group (P<0.05); compared with the model group, the time spent in the middle area increased in the acupuncture group and the NRG1 group (P<0.05). In the spatial exploration stage, compared with the model group, the exploration time in the target quadrant and the frequency of crossing the target platform in the NRG1 group increased significantly (P<0.05); compared with the model group, the total swimming distance in the acupuncture group and the NRG1 group decreased significantly (P<0.05). Compared with the model group, the relative expression levels of NRG1 and ErbB4 mRNA in the NRG1 group increased (P<0.05). Compared with the model group, the relative expression levels of NRG1 protein in the acupuncture group and the NRG1 group increased (P<0.05); compared with the model group, the relative expression levels of ErbB4 protein in the acupuncture group increased (P<0.05).ConclusionAcupuncture can improve the behavioral activities of ASD, especially the core symptom of social interaction disorder, which may be related to the regulation of the NRG1/ErbB4 signaling pathway and the promotion of NRG1 and ErbB4 expression.